OBSERVATION OF DAWN SPECTRAL SHIFTS: TRANSITION FROM FAJAR KAẐIB TO FAJAR ṢADIQ IN DETERMINING THE BEGINNING OF FAJR PRAYER TIME AT THE UIN WALISONGO OBSERVATORY SEMARANG - Fadhel, Muhammad Said; Alawiya, Balkis Sifara (Institut Agama Islam Negeri Batusangkar, 2024)
This research analyzes the color change from false dawn (fajar kaẑib) to true dawn (fajar ṣadiq) in determining the beginning of the Fajr prayer time at the UIN Walisongo Observatory in Semarang. A camera, adjusted to match visual perception, was used to record RGB intensity at regular intervals. Results indicate a significant increase in the red spectrum as true dawn appears, distinct from false dawn. Comparative analysis of RGB ratios, moving averages, and linear fitting identified a pattern of change and an inflection point at a solar altitude of -19.81° or 04:00 WIB, which reliably detects the transition between the two dawns. This method offers a more precise alternative for determining the Fajr prayer time